Modification of alternate wetting and drying (AWD), a proven irrigation strategy for rice production, to reduce the production of mosquitoes that transmit malaria - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The testing of how a modified version of a proven management strategy can have a positive impact on human health is ongoing. Results indicate that AWD can be adjusted is ways that will reduce mosquitos. URL describes the pilot.